What general practitioners know about irritable bowel syndrome: preliminary data from a Romanian province - Dumitraşcu, Dan L.; David, Liliana; Singer, Manfred V. (Journal of gastrointestinal and liver diseases, 2006)
Background and aim. Irritable bowel syndrome (IBS) is a common disorder in Romania, managed frequently by General Practitioners (GPs). It is necessary to assess the knowledge of GPs on IBS. A preliminary investigation was carried out in two Romanian counties. - Methods. One hundred GPs were invited to a two hour, free, updating course on IBS. The participants were asked to fill a questionnaire before and after the course which comprised questions about medical experience, demography, and several multiple-choice questions about GPs´ opinions and awareness. The final question assessed the estimated prevalence of IBS in the practice. - Results. Full responses to both questionnaires were obtained from all attending GPs (n=88). They were 25 males: 63 females, with working experience between 3 and 41 years (mean+SD: 24+11). Apart from 2 (2.4%) who indicated that IBS is a motility disorder (opinion revised after the course), all other GPs considered IBS as a functional disorder. All (100%) opted for the necessity of colonoscopy to diagnose IBS. 98.8% indicated the use of Rome II criteria for the diagnosis of IBS (this survey was done before the availability of Rome III but their advent was mentioned). All (100%) had participated in previous lectures or courses on IBS. 58 (66%) reported the prevalence of IBS in their practice between 1-10%; 16 (18%) between 10-25%; 11 (12.5%) between 25-33%; 3 (3.5%) reported <1%. - Conclusions. The investigated GPs seem to be well trained in recognizing IBS. The majority (66%) estimated the prevalence of this condition as 1-10% in their practice.